Efektivitas media flash card terhadap penguasaan kosakata bahasa Jepang siswa SMA di kota Padang Panjang - Anisa Fadilah; Reny Rahmalina (Universitas Negeri Padang, 2022)
This research is motivated by the students ability to master Japanese vocabulary. Based on interview with teachers and the result of students answer from questionnare, the authors found several obstacles experienced by students, namely first, learning media is needed that attracts students interest. Second, the difficulty of students in remembering japanese vocabulary is still lacking. Third, student learning outcomes on mastery of japanese vocabulary are still low.The purpose of this study to describe the effectiveness flash card media in mastering Japanese vocabulary for Grade Xl IPS class students of SMAN 3 Padang Panjang. This research is Quantitative research using quasi-experiment. This research use posttest-only control group design and use purposive sampling technique. The population of this research are the Xl grade IPS students who consisted of 5 classes, namely Xl IPS1-Xl IPS 5 with the number of 151 people.The samples of this study are class Xl IPS 3 as the control class of 13 people,and class Xl IPS 5 as the experimental class of 14 people.Treatment in this research are 3 times. The instrument of this study use an objective test of 20 questions. Based on the result, so that-test with a significant level of 0,05, it was obtained that tcount<ttabel was1,17<1,70. So that,(H1)is rejected so that it can be concluded that the flash card media is not effective in mastering Japanese vocabulary for the Xl IPS class students of SMAN 3 Padang Panjang.